2015
DOI: 10.1136/gutjnl-2014-308802
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surveillance for Barrett's oesophagus on tumour stage and survival of patients with neoplastic progression

Abstract: OAC is detected at an earlier stage during BO surveillance than in the general population with good survival rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 40 publications
(39 reference statements)
3
52
0
2
Order By: Relevance
“…We also assume that being in an endoscopic surveillance program results in cancer detected at an early stage that will result in the likelihood of curative intervention with surgery. This has been the basis for all the international guidance on BE surveillance but recent data show that actually even though cancer may be detected early there may not actually be a difference in survival in these patients [7]. However, the model aims to capture mean inputs for the average patient and find a balance between a model structure that is too complex or simple dependent, in part, on the data available with which to populate the model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also assume that being in an endoscopic surveillance program results in cancer detected at an early stage that will result in the likelihood of curative intervention with surgery. This has been the basis for all the international guidance on BE surveillance but recent data show that actually even though cancer may be detected early there may not actually be a difference in survival in these patients [7]. However, the model aims to capture mean inputs for the average patient and find a balance between a model structure that is too complex or simple dependent, in part, on the data available with which to populate the model.…”
Section: Discussionmentioning
confidence: 99%
“…They found that OAC was diagnosed at an earlier stage during BE surveillance than in the general population. However, the survival of patients with BE with neoplastic progression was not significantly worse than those of patients without neoplastic progression, and was similar to survival of patients with stage 0 or stage 1 OAC in the general population [7]. In patients with OAC, the prognosis is poor with just over 15% patients being alive at 5 years [8].…”
mentioning
confidence: 99%
“…Two recent studies show that participation in an adequately performed surveillance program reduces mortality from EAC 29 and that EAC is detected at an earlier stage during BE surveillance. 30 In our cohort, most of the patients who progressed were diagnosed with HGD or superficial EAC. A recent meta-analysis shows that PPI therapy is associated with a significantly decreased risk of progression to EAC or HGD.…”
Section: Discussionmentioning
confidence: 99%
“…BM is considered to be a premalignant condition, predisposing patients to an increased risk of oesophageal adenocarcinoma (EAC). Studies have shown that EACs detected in patients with BM undergoing surveillance tend to be of lower stage and to have a better outcome than EACs detected in patients not enrolled in surveillance programmes …”
Section: Introductionmentioning
confidence: 99%